Intensive Self-Efficacy Dengan Kemandirian Belajar Siswa Di Era Pandemi Covid-19 - Niken Septantiningtyas; Afita Khoirun Nisa’ (MANAZHIM, 2022)
This study aims to find out about self-efficacy with student learning independence during the Covid-19 pandemic. The research method used in this research is using qualitative research. Based on the object of study, this research is included in literature research or library research. Literature research is research that comes from libraries and other literacies that are in accordance with the phenomenal being studied. The results of this study show that self-efficacy and student learning independence during the Covid-19 pandemic influence each other. This can be shown by the ability of students who can do independent learning because it is influenced by their self-efficacy which can make the independent learning environment as comfortable as possible so that there is an encouragement of learning motivation that causes them to understand learning easily. This means that self-efficacy and student independence are mutually reinforcing in achieving the success of student learning independence in the era of the covid-19 pandemic.